Existence and exponential stability of periodic solution for fuzzy BAM neural networks with periodic coefficient - Dai-xi, Liao; Li-hui, Yang; Zhang, Qian-hong (Ukrains’kyi Matematychnyi Zhurnal, 2011)
A class of fuzzy bidirectional associated memory (BAM) networks with periodic coefficients is studied. Some sufficient conditions are established for the existence and global exponential stability of a periodic solution of such fuzzy BAM neural networks by using a continuation theorem based on the coincidence degree and the Lyapunov-function method. The sufficient conditions are easy to verify in pattern recognition and automatic control. Finally, an example is given to show the feasibility and efficiency of our results.